Postgraduate Students' Acceptance Degree to Use YouTube Platform to Enhance Research Skills Based on Technology Acceptance Model (TAM) (A Field Study on a Sample of Postgraduate Students in the Faculty of Education at Tishreen University) - اللوحة, محمد; مطيعة أحمد; يوسف شاهين (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research aimed to determine the acceptance degree of postgraduate students to use the YouTube platform to enhance research skills. To achieve the research objectives, a descriptive approach was adopted, and the Technology Acceptance Model (TAM) was used to construct the research tool to measure the impact of the perceived ease of use variable on perceived usefulness, and then measure the impact of the two variables: (perceived ease of use and perceived usefulness) on attitude, followed by measuring the impact of the three variables: (perceived ease of use, perceived usefulness and attitude) on behavioral intention. The research sample consisted of (136) postgraduate students in the Faculty of Education at Tishreen University, and the researcher arrived at the following results: - The sample individuals accept using the YouTube platform to enhance their research skills to a moderate degree. - The postgraduate students' perceptions of the ease of using the YouTube platform to enhance research skills positively affect their perceptions of its usefulness, and predict it. - Both (perceived ease of use and perceived usefulness) variables positively affect the postgraduate students' attitudes towards using the YouTube platform to enhance research skills. - Perceived ease of use has the greatest impact on predicting the postgraduate students' attitudes towards using the YouTube platform to enhance research skills, followed by perceived usefulness. - Both (perceived ease of use, perceived usefulness and attitude) variables positively affect the postgraduate students' behavioral intentions towards using the YouTube platform to enhance research skills in the future. - The perceived usefulness variable has the greatest impact on predicting the postgraduate students' behavioral intentions towards using the YouTube platform to enhance research skills, followed by attitude, and then perceived ease of use. Based on the research results, the researcher provided some recommendations.